Good Corporate Governance dalam Hubungannya dengan Corporate Social Responsibility - Pasuhuk, Lefrand Sermon (JBE (Journal of Business and Economics); Volume 10 No.1, 2011 JBE UNKLAB, 2011)
Good Corporate Governance practices are very important role in a company. Many studies done saying that one way to reduce the practice of earnings management is the implementation of Good Corporate Governance. But from the results of the assessment carried out by some researchers claim that there is still a lack of understanding and practice of good corporate governance within the company. Lately the company is also encouraged to implement Corporate Social Responsibility. Implementation of Corporate Social Responsibility is expected to be done by the company is not for promotional purposes, but really as a form of corporate responsibility to society and the natural environment. Companies with good corporate governance practices that will either implement Corporate Social Responsibility properly in accordance with the purpose of Corporate Social Responsibility is implemented and not to increase the prestige of the company.